If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + x + -1y = 2y + -9 Reorder the terms: 2(-4 + x) + x + -1y = 2y + -9 (-4 * 2 + x * 2) + x + -1y = 2y + -9 (-8 + 2x) + x + -1y = 2y + -9 Combine like terms: 2x + x = 3x -8 + 3x + -1y = 2y + -9 Reorder the terms: -8 + 3x + -1y = -9 + 2y Solving -8 + 3x + -1y = -9 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 3x + 8 + -1y = -9 + 8 + 2y Reorder the terms: -8 + 8 + 3x + -1y = -9 + 8 + 2y Combine like terms: -8 + 8 = 0 0 + 3x + -1y = -9 + 8 + 2y 3x + -1y = -9 + 8 + 2y Combine like terms: -9 + 8 = -1 3x + -1y = -1 + 2y Add 'y' to each side of the equation. 3x + -1y + y = -1 + 2y + y Combine like terms: -1y + y = 0 3x + 0 = -1 + 2y + y 3x = -1 + 2y + y Combine like terms: 2y + y = 3y 3x = -1 + 3y Divide each side by '3'. x = -0.3333333333 + y Simplifying x = -0.3333333333 + y
| -8(x-7)-9=47 | | 2(s+6)+2(s-1)+-4=74 | | (5z-9)(8+z)=0 | | x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 | | 5x=48+x | | 6sec(x)+8=-4 | | 38.00=0.12m+8 | | -3(-6v+6)-v=2(v-8)-7 | | -5/8x-7.5=7.5 | | -5y=6-4y | | 12(n+1)+-11n+2(n+1)=56 | | 7-3(19z-17)=-4(-2z+18) | | 2g=3g-9 |